PESANTREN-BASED RELIGIOUS MODERATION IN SULAWESI: CONTEXTUAL QUR’ANIC VALUES OF AMBO DALLE AND SAHABUDDIN - Muhammad Dirman Rasyid; Muh Ilham Usman; Muhammad Zakir Husain (Universitas Nurul Jadid, 2026)
Religious moderation (wasatiyyah) has become a strategic response to intolerance, exclusivism, and violent extremism in plural societies such as Indonesia, yet its implementation often remains a top-down programme detached from local culture. This study examines how two influential Sulawesi ulama, AGH. Abdurrahman Ambo Dalle of South Sulawesi and Annangguru KH. Sahabuddin of West Sulawesi, contextualised Qur’anic values of moderation through pesantren-based education rooted in Bugis and Mandar traditions. The study aims to reconstruct the interpretive logic and the institutional mechanisms through which moderation was produced and sustained, rather than merely to label the two figures as moderate. Using a qualitative approach combining figure (tokoh) study and the sociology of knowledge, data were drawn from documentation, field observation, and in-depth interviews with family members, colleagues, and former students selected through purposive and snowball sampling across South and West Sulawesi, and analysed through data reduction, thematic categorisation, and interpretive analysis, with source triangulation. The findings suggest that both scholars read verses such as QS. al-Baqarah (2): 143, al-Hujurāt (49): 13, QS. al-Nisā’ (4): 135, and QS. al-Anbiyā’ (21): 107 not as abstract doctrine but as ethical guidance embodied in pedagogy, vernacular preaching, and community mediation. The study contributes a contextual, sociological account of how localised tafsīr and grassroots authority can institutionalise a durable, culturally grounded model of moderation.",